Analysis of the legal and organizational framework for ensuring the security of personal data - E. A. Ovchinnikova; E. A. Semenova; V. V. Tsapleva (Современная наука и инновации, 2024)
The paper analyzes the features of the application of the legal framework for ensuring the security of PD, as well as reveals the essential organizational aspects of planning a PD protection system in an organization. The authors analyze certain aspects of legal regulation that have a significant impact on the choice of organizational measures to protect PD: setting the limits of the RF legislation in the field of PD; establishment of categories of PD and the main sources of legal regulation corresponding to them; features of legal regulation of the processing of certain categories of PD. Structurally and logically, the work is divided into two main parts: legal measures to ensure the security of PD, organizational measures for planning the protection of PD. In general, the authors of the article analyze legal, organizational and planning measures to ensure the security of personal data that can be implemented in an organization.